Clinical Oral Medicine and Pathology - Bruch, Jean M.; Treister, Nathaniel Simon; SpringerLink (Online service) (Totowa, NJ : Humana Press, 2010)
Clinical Oral Medicine and Pathology, is a clinically relevant and accessible resource for health care professionals that truly bridges the worlds of dentistry and medicine. This handbook of oral medicine and oral pathology serves as a highly readable guide for diagnosis and treatment of commonly encountered oral conditions. The volume is organized by grouping clinical entities under easily recognizable, diagnostically related headings and subheadings and allows the busy clinician to quickly reference and identify a lesion of interest. Concise descriptions of each entity provide background information and treatment recommendations while including specific guidelines on diagnosis, management, and follow-up. The authors of this text both have extensive training in the fields of oral pathology, dentistry, oral surgery and otolaryngology, and provide a comprehensive approach to the practice of oral medicine for all those who are likely to encounter diseases of the oral cavity in their daily practice.
Normal Anatomy -- Variants of Normal and Common Benign Conditions -- Diagnostic Tests and Studies -- White Lesions -- Immune-Mediated and Allergic Conditions -- Pigmented Lesions -- Oral Infections -- Salivary Gland Disease -- Oral Cancer -- Orofacial Pain Conditions -- Oral Manifestations of Systemic Disease -- Prescribing Guidelines for Commonly Used Medications.
Keywords: Medicine; Otorhinolaryngology; Head -- Surgery; Pathology; Surgery; Medicine & Public Health; Pathology; Otorhinolaryngology; Head and Neck Surgery; Oral and Maxillofacial Surgery